Socioeconomic Risk Factors for Long-Term Mortality after Pulmonary Resection for Lung Cancer: An Analysis of More than 90,000 Patients from the National Cancer Data Base - Khullar, Onkar V (J Am Coll Surg, 2014)
BACKGROUND: Several clinical variables, such as tumor stage and age, are well-established factors associated with long-term survival following surgical resection of lung cancer. Our aim was to examine the impact of other clinical and demographic variables, controlling for known predictors of long-term survival, in order to investigate how outcomes varied according to important non-clinical factors. STUDY DESIGN: The National Cancer Data Base, jointly supported by the Commission on Cancer of the American College of Surgeons and the American Cancer Society, was utilized to identify patients undergoing pulmonary resection for lung cancer and perform a retrospective cohort study. The cohort consisted of patients diagnosed with NSCLC from 2003–2006 who underwent resection, as overall survival data are available only for patients diagnosed through 2006. A Cox proportional hazards survival model was used to examine factors associated with risk of mortality. RESULTS: A total of 92,929 patients were identified as diagnosed during the study period and undergoing surgical resection for lung cancer. On multivariable analysis, several socioeconomic factors such as lack of insurance, lower income, less education, and treatment at community centers vs. academic/research programs predicted worse overall survival after controlling for disease characteristics known to be predictors of worse survival, such as tumor stage, histology, age, and extent of resection. CONCLUSIONS: Diminished long-term survival after pulmonary resection was associated with a number of socioeconomic factors. To date, this represents the largest database analysis of long-term mortality in patients undergoing surgical resection for lung cancer. The disparities in survival outcomes reported here require further, detailed investigation.